2012
DOI: 10.1097/mjt.0b013e318205427a
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Studies in Women of 2 Novel Oral Formulations of Tranexamic Acid Therapy for Heavy Menstrual Bleeding

Abstract: Two randomized, open-label clinical studies involving healthy female volunteers aged 18-45 years (study 1, N = 32; study 2, N = 40) are described, which characterize the pharmacokinetics and steady-state dosage regimen performance of 2 novel, modified-release tranexamic acid tablet formulations. The objective of these studies was to identify the optimum product formulation to advance into late-phase clinical trials for heavy menstrual bleeding. For study 1, participants received single 1.3-g doses (2 650-mg ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…After screening titles and abstracts, 51 studies were excluded because no pharmacokinetic data were reported and 10 studies were excluded because the study population was not healthy human volunteers. A total of 10 studies were therefore deemed eligible for full-text retrieval [19][20][21][22][23][24][25][26][27][28]. Among those, one study was excluded for wrong participant population [19]; one because the study drug was a prodrug [21] and another one because tranexamic acid was used for local treatment [20].…”
Section: Pharmacokinetic Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening titles and abstracts, 51 studies were excluded because no pharmacokinetic data were reported and 10 studies were excluded because the study population was not healthy human volunteers. A total of 10 studies were therefore deemed eligible for full-text retrieval [19][20][21][22][23][24][25][26][27][28]. Among those, one study was excluded for wrong participant population [19]; one because the study drug was a prodrug [21] and another one because tranexamic acid was used for local treatment [20].…”
Section: Pharmacokinetic Modellingmentioning
confidence: 99%
“…Data were available from 10 participants in four studies for the IV route, six participants in two studies for the IM route and 114 participants in six studies for the oral route. Moore et al [24] also investigated the pharmacokinetics of modified-release tablets but only data from the immediate release formulation were exploited in the present study; similarly, Sindet-Pedersen [28] was also interested in the use of local application of TXA in mouth rinsing solutions which was not considered for this study. A total of five participants received several doses from different routes in cross-over design studies.…”
Section: Data Availablementioning
confidence: 99%
“…Pharmacokinetics and tolerability of tranexamic acid were evaluated for both modified-immediaterelease (MIR) and delayed-release formulations. 61 Dosages of 1.3 g 3 times/day were used to achieve therapeutic concentrations of 5-15 µg/ml. Evaluations occurred in both the fed and fasted state and after single and multiple doses.…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…It is available as a 650-mg oral tablet, and two tablets are taken three-times per day for up to 5 days during menstruation. The novel, modified-release TA formulation results in controlled dissolution of the drug, which reduces the gastrointestinal adverse events (AEs) that limit patient tolerability of immediaterelease TA; in Phase I studies, these formulations were demonstrated to be bioequivalent [7].Two pivotal Phase III studies have shown TA to be an effective nonhormonal treatment for HMB [8,9], and long-term data have demonstrated the tolerability of TA, with the most frequent AEs being headache, nasal and sinus symptoms, and back pain [10,11]. This pooled analysis of the two pivotal Phase III TA studies evaluated the efficacy and safety of TA in women with HMB and fibroids [8,9].…”
mentioning
confidence: 99%